2023
DOI: 10.3390/life13051217
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Evaluation of Antimicrobial Properties of the Wild Medicinal Mushroom Ganoderma lucidum Growing in Northern Moroccan Forests

El Hadi Erbiai,
Benoutman Amina,
Abbassi Kaoutar
et al.

Abstract: Ganoderma lucidum is an extensively famous medicinal mushroom distributed worldwide. Despite being widely grown in Moroccan forests, there are no studies on its nutritional, nutraceutical and pharmaceutical values. Herein, the objective of this study was to investigate the chemical characterization and antimicrobial properties of G. lucidum methanolic extract. Total phenolic, flavonoid, tannin, ascorbic acid and carotenoid contents were determined by spectrophotometry. The results revealed that the most preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Consequently, antimicrobials derived from fungi have garnered much attention in recent years. The present study shows that GLME could combat various diseases caused by pathogenic microorganisms 52 , 53 . Overall, our data suggest that GLME may be a novel strategy for treating cancer and bacterial infections because it contains a wide range of anticancer and antibacterial compounds.…”
Section: Discussionmentioning
confidence: 54%
“…Consequently, antimicrobials derived from fungi have garnered much attention in recent years. The present study shows that GLME could combat various diseases caused by pathogenic microorganisms 52 , 53 . Overall, our data suggest that GLME may be a novel strategy for treating cancer and bacterial infections because it contains a wide range of anticancer and antibacterial compounds.…”
Section: Discussionmentioning
confidence: 54%
“…In comparison, Janjušević et al reported by HPL-MS/MS that quercetin (29.30 μg g −1 ) and catechin (21.90 μg g −1 ) were the primary flavonoid constituents of C. versicolor methanol extract from Fruška gora, Vojvodina, Northern Serbia [ 21 ]. Moreover, Erbiai et al confirmed that quercetin had the highest content (947.2 μg g −1 dw) at the G. lucidum methanol extract from the Biological and Ecological Interest Site (SIBE) of Koudiat Taifour in northwestern Morocco [ 33 ]. In this extract, the presence of rutin, narigenin, apigenin, and kaempferol was also detected [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Erbiai et al confirmed that quercetin had the highest content (947.2 μg g −1 dw) at the G. lucidum methanol extract from the Biological and Ecological Interest Site (SIBE) of Koudiat Taifour in northwestern Morocco [ 33 ]. In this extract, the presence of rutin, narigenin, apigenin, and kaempferol was also detected [ 33 ]. However, Onar et al reported that the content of epicatechin, catechin hydrate, and quercetin dihydrate determined by HPLC was ≤1 ppm in F. pinicola ethanol extract from Belgrad Forest, Istanbul [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, further research is needed to fully understand the mode of action and various applications. G. lucidum has been shown to possess potent antimicrobial activity against a variety of bacteria, viruses, and fungi [ 92 ]. There are several potential future developments for G. lucidum as an antimicrobial agent that could be possible, such as the development of new antibiotics, natural preservatives, bioremediation, and personal care products [ 2 , 197 ].…”
Section: Future Scenarios Of Secondary Metabolites As Antioxidants An...mentioning
confidence: 99%